Young adults face the future of the United States: Perceptions of its promise, perils, and possibilities. (May 2022) - Kantenbacher, Joseph; Miniard, Deidra; Geiger, Nathaniel; Yoder, Landon; Attari, Shahzeen Z.
Abstract: There are a variety of current challenges that will shape our future, such as climate change impacts, socio-economic disparities, the role of technology in society, and changing population dynamics. As ideas about the future influence actions taken today, it is important to study what possible futures young adults anticipate and how they believe those futures could be realized. In 2019, using an in-person paper survey, we asked students ( N  = 193; ages 18–26) to describe their best, most-likely, and worst possible futures for the United States in either the year 2050 or 2100. Participants were also asked questions to explore what would need to happen to achieve these futures and the actors who have influence in shaping the future. Here we explore their description of these future scenarios and pathways. Our participants' images of the future are heavily infused with concepts related to environmental sustainability, technology, and social dynamics. Further, participants frequently expressed the belief that governance, technological developments, and individuals were key factors that will determine the contours of the future. The images of the future collected by our work can help to engage productively with young adults in addressing today's pressing challenges. Highlights: Young adults see the environment as a key term for understanding the future. Waste, not climate change, is the most prominent environmental issue. Government and technology are viewed as most likely factors to shape the future. Reported optimism about the future but depictions of the future less optimistic.